Climate Change Education: A Focus on Socio-Ecological Challenges - White, Peta J. (Universitas Muhammadiyah Surakarta, 2025)
Educating in the Anthropocene is challenging! We experience human systems entangling with Earth systems regularly and often negatively and with such force and impact. How are we preparing our future citizens to be able to make responsible decisions when the future is uncertain and change inevitable. Our young people must be able to interpret climate data and manage misinformation accurately to disrupt the insidious strategies of the fossil fuel companies and oligarchs. As educators it is up to us to shift the focus towards understanding how the challenges we face are best framed as socio-ecological (not environmental issues) and that although our futures are uncertain in many ways, change is inevitable. I have found that teaching climate impacts doesn’t increase competencies for change and action but increases anxiety and disillusionment. Leverage for curriculum change is coming, via the OECD PISA 2025 Science Framework - specifically 'Agency in the Anthropocene' (White et al, 2023) and should see curricula responding in the medium term. In the short term we must support schools to enable teachers to become informed and resourced to provide high-quality climate change education. Action oriented strategies for learning develop learner agency (and compel teacher agency) and may lead to schools becoming climate education hubs for communities.In Australia, we are advocating for renewed policy (curriculum and beyond) that will enable and support (and resource) climate change education. In this presentation I will outline the research that informs the policy drive as well as the classroom practices that empower teachers and students to become informed future citizens who make responsible decisions.